Impact of changes caused by the pandemic on the current state and development of oil and gas companies - Mugtabarovna Gaisina, Lyutsiya; Shaykhislamov, Rafael Badretdinovich; Semenova, Lenara Mauzatovna; Yaminova, Svetlana Aleksandrovna; Musina, Eliza Rinatovna; Lopatina, Elena Valentinovna (Nexo Revista Científica, 2022)
The results of sociological research in the oil and gas industry are presented in the article, revealing the recent social changes with a major impact on the Russian oil and gas market and the personnel management system. The article deals with demographic reasons and the role of the pandemic, which endangered post-millennials. The authors reevaluate the impact of digitalization on the Generation Z, which led to the reduction of working digital natives, since they will not live to work, but they will work to live. Gender, age, and professional characteristics of employees in oil and gas companies have been analyzed, as well as the current state and development trends of the labor market. The article emphasizes the priority of individual characteristics of "digital people", rather than staff numbers and pay level of the employees. This view resulted from the new reality of COVID-19 pandemic, geopolitical trends, sanctions policy, the global spread of digital technologies, mixing of socio-economic orientations and personal development. These people are unwilling to depend on anyone, but the ideal manager for them is the one who sets tasks most clearly and definitely.